Ultrasonographic Appearances of Cervical Lymph Nodes in Healthy Turkish Adults Subpopulation: Preliminary Study - NAMDAR PEKİNER, FİLİZ MEDİHA (BENTHAM SCIENCE PUBL LTD, 2017)
Objectives: The aim of the study was to assess whether there was any relation between age, gender and body mass index (BMI) and nodal forms and vascular type in healthy Turkish adults. Study Design: Three neck areas in 25 wholesome patients who were aged from 21 to 58 years, were assessed by gray-scale and color doppler ultrasonography. Ultrasonographic examinations were performed using an ALOKA Prosound Alpha 6 (Hitachi Aloka Medical Systems, Tokyo, Japan) and the images were obtained with a 7.2 MHz linear array transducer. Hajek's categorization of cervical lymph nodes for sonographic analysis was used. The ultrasonographic characteristics like size, shape, short axis/long axis ratio (S/L), hilum were evaluated. Ultrasonographic examinations of upper cervical, submandibular and submental lymph nodes were carried out and recorded. Results: The mean age of patients was 31.84 +/- 12.80 years. The ratios of lymph nodes with avascular pattern were 96% for the upper cervical lymph area, 92% for the submandibular area and 96% for the submental area. The lowest and highest ratios of short to long axis diameter (S/L) were calculated as 0.18 and 0.66 in all areas. Most normal nodes in the study were oval with an S/L ratio of less than 0.5. Conclusion: Normal cervical lymph nodes are oval, with an unsharp border and an echogenic hilum but no relation between the age, gender and BMI. Also ultrasonography is an applicable imaging modality for the examination of cervical lymph nodes. However, the deficiency in the number of patients might not allow to generalise our findings to the general populations.
Keywords: Cervical; Lymph nodes; Ultrasonography; Normal anatomy; BODY-MASS INDEX; SONOGRAPHIC APPEARANCES; NECK; ULTRASOUND; BENIGN; AGE; DIFFERENTIATION; ASSOCIATION; METASTASIS; CANCER